Recruitment and Pay at the Establishment Level: Gender Segregation and the Wage Gap in Portugal - José A. Cabral Vieira; Ana Rute Cardoso; Miguel Portela (Institute for the Study of Labor (IZA), 2003)
This paper aims at quantifying the trend in worker segregation at the establishment level and its impact on wages in Portugal over a fifteen year period. We concentrate on the gender dimension, to answer the questions: have changes in recruitment policies at the establishment level resulted in higher gender segregation in the labour market? What is the impact of segregation on wages? Is that impact different for men and women? A large linked employer-employee data set is used. Systematic and random components of segregation are computed. We use standard wage decomposition techniques to evaluate the impact of the composition of the labour force at the establishment level on wages. Results reveal a high degree of systematic gender segregation. A higher proportion of females in the establishment lowers females' wages while, on the contrary, it raises males' wages. Between mid-80s and late-90s, the contribution of the gender composition of the workforce within the establishment to the wage gap increased, though fluctuating within that period. The evidence gathered lends support to the taste-based model of employer behaviour.
Keywords: D21; J7; J31; 330; systematic segregation; random segregation; gender; wage inequality; Arbeitsnachfrage; Geschlechterdiskriminierung; Lohndifferenzierung; Schätzung; Arbeitsmarktdiskriminierung; Portugal